HARAPAN MEMBUATKU BERTAHAN: HARAPAN AKADEMIK MEMPREDIKSI GRIT AKADEMIK - Aryan Muhaimin Saputra; Sumedi P Nugraha (Universitas Gunadarma, 2023)
Research shows that students with academic grit have better achievement, learning regulation, and resilience abilities than students without academic grit. Even so, research results show that it is still rare to find academic grit in a person. Academic hope is a positive psychological variable that has many benefits to positive educational variables and has been proven to be able to predict academic grit. This study tries to look back at the ability of academic hope to academic grit in middle school students. The participants used in this study were 194 students of SMK-SMAK Makassar. There were two instruments distributed to SMK-SMAK Makassar students, namely the academic hope scale and the academic grit scale which were distributed to research respondents. Tests on the data collected show that academic expectations can provide significant academic grit and make a large effective contribution. There are two aspects of academic expectations, namely pathway and agency. Path analysis as an additional analysis to see the predictive ability of each aspect of academic expectations shows that the path makes a large effective contribution, while the agency makes a small effective contribution. These results show the balance of academic expectations of one's academic grit.